The Effect of 11% VAT on the Consumer Purchasing Power of Beauty Products in Klaten Regency - Rizky Windar Amelia (Universitas Nahdlatul Ulama Sidoarjo, 2024)
The online business continues to increase, the government has issued legal policies, one of them is VAT policy. The government also officially increased VAT from 10% to 11%. This VAT policy directly increases the value of goods because consumers bear the VAT. This study aims to analyze the effect of 11% VAT on the purchasing power of beauty products in Klaten Regency. This research uses a quantitative method with regression analysis. The sampling technique used was purposive sampling. Data was collected through a questionnaire distributed to 100 respondents who were consumers of beauty products in Klaten Regency. The data was analyzed using the t-statistical test and the coefficient of determination test (R2). Data processing in using SPSS software version 26.0 for Windows. The results of this sudy show that 11% VAT has a positive and significant effect on the purchasing power of beauty products in Klaten Regency. Based on the results of the analysis coefficient of determination R2, it shows that peoples purchasing power is influenced by 11% VAT by 5.7%. The remaining 94.3% is influenced by other variables not discussed in the research. This research contributes to a deeper understanding of the impact of tax policy on communities and businesses at the local level, with the hope of providing guidance for more inclusive and sustainable policies in the future.